HEALTH EDUCATION TO PREVENT DIABETES; A STUDY AMONG STUDENTS WITH PREDIABETES IN SURAKARTA, INDONESIA - Agista Delima Permadani; Bayu Cahyo Oktafian (Proceedings of the International Conference on Applied Science and Health, 2017)
Background: Pre-diabetes is a condition where blood glucose above normal, called as a pre-diagnosis diabetes. Without any effort to prevention, pre-diabetes will become diabetes within 5-10 years. From the preliminary study, there are 61 students in Nursing Program of Health Polytechnic Surakarta diagnosed with high blood glucose level. Early prevention with health education on the prevention of diabetes, namely physical activity and diet. Aim: The purpose of this study is to determine the effect of health education to prevent diabetes among students with high blood glucose level. Method: This research employed a quasi-experimental design with one group pretest and posttest. The fasting blood glucose (FBG) was measured before and after health education. A total of 30 students, with pre-diabetes risk, from Nursing Program of Health Polytechnic Surakarta, selected by purposive sampling, was involved before and after the program. The blood glucose level was measured using blood glucose meter, with three replications. Health education was given using SAP (Events Unit Extension), leaflet and power point slides. Material of the health education program on primary prevention of DM was provided for 20 minutes only 1 time. Paired T-Test was used to find the significant differences of average levels of fasting blood glucose levels before and after given health education. Results: The level of fasting blood glucose levels respondents before being given health education was 95.30 ± 2.67 mg/dL. While after given health education, the glucose level decreased 1.52 mg/dL to the level of 93.77 ± 2.94 mg/dL. Through paired T-test, it is noted that the decline was significant (p value = 0.014). However, the drop of fasting blood glucose levels among students diagnosed with pre-diabetes cannot ensure the level to the non-diabetes risk. Conclusion: This results supports the provision of health education on the prevention of diabetes. It suggest the need of providing health education for early prevention.